2022
DOI: 10.3389/fgene.2021.749296
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Roles of Circular RNAs in Vascular Smooth Muscle Cell Dysfunction

Abstract: Atherosclerosis is the major pathophysiological basis of cerebrovascular and cardiovascular diseases. Vascular smooth muscle cells (VSMCs) constitute the main structure of vasculature and play important roles in maintaining vascular tone and blood pressure. Many biological processes and cellular signaling events involved in atherosclerogenesis have been shown to converge on deregulating VSMC functions. However, the molecular mechanisms underlying dysfunctional VSMC in atherosclerosis are still poorly defined. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…In the regulatory mechanisms of atherosclerosis (AS), several circRNAs have been implicated. Pu Z et al reported the involvement of circACTA2, circ-SATB2, and circCCDC66 in regulating vascular smooth muscle cell (VSMC) growth through miRNA sponging, thereby affecting AS formation [135]. Moreover, circRNAs have been shown to influence the onset and development of AS by regulating processes such as apoptosis, inflammatory response, and oxidative stress [136].…”
Section: Atherosclerosis (As)mentioning
confidence: 99%
“…In the regulatory mechanisms of atherosclerosis (AS), several circRNAs have been implicated. Pu Z et al reported the involvement of circACTA2, circ-SATB2, and circCCDC66 in regulating vascular smooth muscle cell (VSMC) growth through miRNA sponging, thereby affecting AS formation [135]. Moreover, circRNAs have been shown to influence the onset and development of AS by regulating processes such as apoptosis, inflammatory response, and oxidative stress [136].…”
Section: Atherosclerosis (As)mentioning
confidence: 99%
“…Circular RNAs (circRNAs) are endogenous regulatory RNAs, which are covalently closed loops after reverse splicing due to the lack of 3’-poly-a tail and 5’- cap ( 80 ). Studies have demonstrated that most circRNAs regulate gene expression post-transcriptionally through sponging microRNAs (miRNAs), for example circACTA2, circ-SATB2, circDiaph3, circ_0020397, circTET3, circCCDC66, and miR-541, miR-195, miR-146a, miR-133, miR-214, miR-34a ( 81 , 82 ). It is suggested that circRNAs and miRNAs may be a new target spot and a new hot point in preventing dysfunctional VSMCs in AS.…”
Section: Mechanisms Of Vsmcs In Asmentioning
confidence: 99%
“…circmTOR (circ_0009805) is overexpressed in severe preeclamptic placentas [309]. CircmTOR (circ_0009792) is upregulated in the proliferation of vascular smooth muscle cells [310] (Table 8). Other cell functions were rarely reported for this circmTOR.…”
Section: Akt Effectorsmentioning
confidence: 99%